Fisheries policies on government leased fishponds a review - Seville, Hitler S. (University of the Philippines in the Visayas, 2001)
A study to determine the levels of knowledge and understanding of the policies related to Fishpond Lease Agreement (FLA) was conducted among three types od respondents categorized as Individually-Owned Fishpond Operators; Family-Owned Fishpond Operators and Government Personnel from DA-BFAR, Department of Environment and Natural Resources, Department of Public Works and Highways and Local Government Units Personnel who are involved in the MakaMASA Program-Fisheries. Results of the study showed that government personnel have the highest level of knowledge and understanding over fishpond operators in most policies evaluated. Individually owned Fishpond Operators, on the other hand, had the lowest level of knowledge and understanding. In this regard, the government through the Bureau of Fisheries and Aquatic Resources which is the lead agency in the implementation of the FLA policies, should take the initiative in making all fishpond lease holders and involved government personnel fully aware of the proper interpretation of the laws, rules and regulations governing FLAs to develop all the leased areas to make them productive.